Dialektik des Globalen. Kernbegriffe: Land - Sippel, Sarah Ruth / Böhme (Dialektik des Globalen. Kernbegriffe, 2021)
This volume shows how land is currently being renegotiated as a collective commodity, private property, fertile soil for human existence, or as an object of financial investment by identifying the ideas of space and spatial order on which these processes of negotiation are based.